2012
DOI: 10.2147/opth.s34962
|View full text |Cite
|
Sign up to set email alerts
|

Vitrectomy for optic disc pit-associated maculopathy with or without preoperative posterior vitreous detachment

Abstract: BackgroundThe purpose of this study was to evaluate the efficacy of pars plana vitrectomy for the treatment of optic disc pit-associated maculopathy with or without preoperative posterior vitreous detachment.MethodsWe reviewed the clinical records of four consecutive patients who underwent pars plana vitrectomy in one eye for the treatment of optic disc pit-associated maculopathy, with an emphasis on the preoperative condition of the posterior hyaloid membrane.ResultsTwo of four eyes were confirmed to have an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Eleven months into the post-operative period, the macula was reattached. The subsequent reduction of the diameter of the optic pit suggests potential pre-operative traction from the vitreous in maintaining the patency of the pit (Figure 2) The pre-operative absence of a posterior vitreous detachment in our case may also have contributed to our good surgical result, as this was reported to be a positive prognostic factor by Haruta et al [5].…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Eleven months into the post-operative period, the macula was reattached. The subsequent reduction of the diameter of the optic pit suggests potential pre-operative traction from the vitreous in maintaining the patency of the pit (Figure 2) The pre-operative absence of a posterior vitreous detachment in our case may also have contributed to our good surgical result, as this was reported to be a positive prognostic factor by Haruta et al [5].…”
Section: Discussionsupporting
confidence: 49%
“…Treatment modalities reported for ODP maculopathy include various combinations of PPV, gas tamponade, laser photocoagulation to the temporal juxtapapillary area, internal limiting membrane (ILM) peeling, internal drainage of submacular fluid or macular scleral buckling procedure [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, vitreomacular or vitreopapillary traction secondary to incomplete vitreous separation is another plausible mechanism. [ 1 , 26 30 ] [ 31 ] In our series, 7/11 (63.6%) of the eyes with peripapillary schisis had evidence of adherent vitreous with traction at the nerve in contrast to 13/979 (1.33%) of eyes without peripapillary schisis, while 404/979 (41.3%) eyes without peripapillary schisis had vitreopapillary adhesion without traction. In a series of 13 POAG eyes with microcystic INL changes similar to schisis, Hasegawa et al reported that the vitreous was attached in the area of microcystic INL spaces in 76.9% of eyes.…”
Section: Discussionmentioning
confidence: 62%
“…However, all three eyes with maculopathy belonged to young patients without PVD, suggesting an association of the posterior hyaloid adhering to the optic disc with the pathogenesis of maculopathy. In addition, of four eyes with optic disc pit maculopathy, two without preoperative PVD showed resolution of maculopathy after PPV with induction of PVD, whereas the other two eyes with no resolution belonged to elderly patients having PVD before surgey 10. Taken together, this suggests that in young patients without PVD, the posterior hyaloid adhering to pits may exert traction on the disc and cause maculopathy, whereas, in elderly patients with PVD such as ours, remnant tissue contraction on the disc is likely to be a driving force similar to the posterior hyaloid or epiretinal membranes.…”
Section: Discussionmentioning
confidence: 85%
“…In two eyes with glaucoma developing retinal schisis without PVD, retinal schisis was reduced after PPV with intraoperative PVD formation 3. Based on these observations, it is suggested that traction of the posterior hyaloid to the optic disc plays a role in the onset of retinal schisis associated with optic disc pits or a glaucomatous disc without PVD 1,8,10…”
Section: Discussionmentioning
confidence: 98%